2006
DOI: 10.1002/bit.21056
|View full text |Cite
|
Sign up to set email alerts
|

A complete enzymatic recovery of ferulic acid from corn residues with extracellular enzymes fromNeosartorya spinosa NRRL185

Abstract: An economic ferulic acid recovery from biomass via biological methods is of interest for a number of reasons. Ferulic acid is a precursor to vanillin synthesis. It is also a known antioxidant with potential food and medical applications. Despite its universal presence in all plant cell wall material, the complex structure of the plant cell wall makes ferulic acid recovery from biomass a challenging bioprocess. Previously, without pretreatment, very low (3-13%) recovery of ferulic acid from corn residues was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…At least 40-60% of FA and lower amounts of p-coumaric acid were, however, released from steamexploded wheat straw by two purified A. niger FAEs (Benoit et al 2006). FAEs are generally regarded as plant cell wall loosening enzymes providing better accessibility of glycoside hydrolases to the polysaccharides (Wong 2006;Shin et al 2006;Faulds 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 40-60% of FA and lower amounts of p-coumaric acid were, however, released from steamexploded wheat straw by two purified A. niger FAEs (Benoit et al 2006). FAEs are generally regarded as plant cell wall loosening enzymes providing better accessibility of glycoside hydrolases to the polysaccharides (Wong 2006;Shin et al 2006;Faulds 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The use of whole cell enzyme complement versus an artificial assembly a All processes were performed at 45°C for 24 h in a reaction mixture containing 5 ml of 100 mM NaAc reaction buffer (pH 5.0) and 150 mU of A. alternata FAE and 3.7 U of xylanase. All the data were reported as mean ± SD with 3 replicates b Bran was not autoclaved before enzymatic hydrolysis c Bran was autoclaved before enzymatic hydrolysis d Enzymatic hydrolysis was performed with combination of A. alternata extracellular enzymes and 10 U of T. viride xylanase of cloned enzymes in a cocktail format likely offers the advantage of low-cost processing (Shin et al 2006;Panagiotou et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid is a well known antioxidant with potential for food and medical applications [45]. Gallic acid is commonly used for testing phenolic content.…”
Section: The Comparison Of Gallic Acid and Ferulicmentioning
confidence: 99%
“…Shin et al described the complete recovery of ferulic acid from corn bran with the use of a pool of enzymes obtained from a filamentous fungus and its bioconversion into vanillin with a yield of 43%. 13 Recent research work in the authors' laboratory has shown that crude wheat bran hydrolyzates, obtained with the use of a mixture of commercial enzymes possessing esterase activity, could be used as the source of ferulic acid for vanillin production. 15 A maximum vanillin molar yield of 50% was obtained using resting cells of an Escherichia coli strain carrying the genes for the bioconversion of ferulic acid into vanillin of Pseudomonas origin; 16 the low yield obtained was ascribed to the reduction of most of the vanillin produced to the side product vanillyl alcohol.…”
Section: Introductionmentioning
confidence: 99%